2015
DOI: 10.1614/ws-d-14-00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Soybean with Imazethapyr Applied Alone or in Tank Mix with Saflufenacil/Dimethenamid-P

Abstract: Saflufenacil/dimethenamid-P is a relatively new prepackaged herbicide mixture that has the potential to provide enhanced weed control in soybean when tank-mixed with reduced doses of imazethapyr. Six field experiments were conducted over a 3-yr period (2011, 2012, and 2013) near Ridgetown and Exeter, Ontario, Canada, to determine the dose of imazethapyr, applied PRE, that must be added to saflufenacil/dimethenamid-P (245 g ai ha−1) to provide effective weed control in soybean. The predicted dose of imazethapyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Also, fomesafen provided ≥86% control of yellow foxtail, green foxtail, and barnyardgrass 40 DAPRE (Table 4). Walsh et al (2015) also reported acceptable grass control (≥75%) and improved soybean yields with PRE application of PPO herbicides in a tank mix with imazethapyr. Moreover, imazethapyr in mixtures with PPO herbicides and metribuzin provided complete control of green foxtail at two weeks after soybean emergence (Belfry et al, 2016).…”
Section: Grass Weed Controlmentioning
confidence: 87%
See 1 more Smart Citation
“…Also, fomesafen provided ≥86% control of yellow foxtail, green foxtail, and barnyardgrass 40 DAPRE (Table 4). Walsh et al (2015) also reported acceptable grass control (≥75%) and improved soybean yields with PRE application of PPO herbicides in a tank mix with imazethapyr. Moreover, imazethapyr in mixtures with PPO herbicides and metribuzin provided complete control of green foxtail at two weeks after soybean emergence (Belfry et al, 2016).…”
Section: Grass Weed Controlmentioning
confidence: 87%
“…Results showed the effective broad‐spectrum weed control when premixes from Group 2 (ALS‐inhibitors), Group 5 (Photosystem II [PSII]‐inhibitors), Group 14 (protoporphyrinogen oxidase [PPO]‐inhibitors), and Group 15 (long‐chain fatty acid‐inhibitors) herbicides. Similarly, others reported that PRE application of PPO herbicides tank‐mixed with ALS‐inhibiting herbicides provided an effective control of broadleaf species (Belfry et al, 2015; Walsh et al, 2015); including kochia, Russian thistle ( Salsola tragus ), field bindweed ( Convolvulus arvensis ), velvetleaf, common lambsquarters, and yellow sweetclover ( Melilotus officinalis ) in Nebraska (Knezevic et al, 2009). Hausman et al (2013) also reported that PRE‐applied metribuzin and flumioxazin alone provided 92% waterhemp control at 60 DAPRE in soybean.…”
Section: Broadleaf Weed Controlmentioning
confidence: 98%
“…ha -1 (Belfry et al, 2015). The application of imazethapyr, molecule that belongs to the ALS inhibitor group, has also caused injuries in soybean (Walsh et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in soyabean, imazethapyr applied PRE at a dose of 100 g a.i. ha −1 reduces the density and weight of C. album , Ambrosia artemisiifolia (common ragweed), S. viridis (green foxtail) and Abutilon theophrasti (velvetleaf) by up to 80% (Walsh et al ., ). In another study, imazethapyr applied PRE at a dose of 0.067 kg a.i.…”
Section: Discussionmentioning
confidence: 97%
“…Imazethapyr is an acetolactate synthase (ALS)‐inhibiting herbicide and belongs to the imidazolinone group registered for use in soyabean at 75–100 g a.i. ha −1 (Walsh et al ., ). Imazethapyr controls a wide range of grass and broad‐leaved weeds and can be applied in pre‐plant, pre‐plant incorporated (PPI), PRE and POST treatments (Cantwell et al ., ).…”
Section: Introductionmentioning
confidence: 97%